Shariah Compliant Macaulay’s Duration Model Testing: Evidence from Islamic banks in Indonesia - Shah, Syed Alamdar Ali; Sukmana, Raditya; Fianto, Bayu Arie (Universitas Muhammadiyah Surakarta, 2021)
The purpose of this research is to test Shariah compliant duration models on Islamic banks in Indonesia. This will be achieved using data of earning assets and risk bearing liabilities of Indonesian Islamic banks from 2009 to 2019. Using multiple regressions the results suggest that Shariah compliant duration models are robust to calculate duration of earning assets, return bearing liabilities and Islamic banks. This research adds to the previous research of testing Shariah compliant duration model. Ultimately, it will improve profitability, risk efficiency and Shariah efficiency by improved Shariah compliant measures of risk management. This will ultimately improve market capitalization and returns stability in the long run. A major limitation of the study is very short length of data of Islamic banks. Still another limitation is difference in commencement of business of various Islamic banks that makes length of data unequal.